Estrategía didáctica estético-artística para la valoración del patrimonio cultural en los estudiantes de quinto grado de la Unidad Educativa Intercultural Bilingüe Surupucyu de la provincia Bolívar cantón Guaranda parroquia Guanujo, periodo 2024 - Gaibor Montoya, Lisseth Leonela (2025)
This research responds a need to work on a teaching strategy directed to train aestetitc- arthistic sensibility of cultural heritage of Fifth-Year basical education students. Aesthetic Sensibility is a fundamental component of development of educative process; therefore, It is a responsability of the educational unit speccially teachers to guide students to react properly such as emotionally as intelectually before beauty. In other words, establish the way for the individual to connect with a piece of art and enjoy its aesthetic pleasure. This investigative process used a combined approach, related to reality and knowledge; an a quantitative an qualitative approach. On the other hand, contributions to etongrafic reseach were used. In terms of the methods that guided this work, the analytical, descriptive and hermeneutic methods stand out, the latter being of great importance because it is associated with the art of understanding and interpreting what is being studied. With regard to the techniques and instruments used to collect the information, this was done through surveys and interviews, which were processed with the tools of descriptive statistics using frequency tables, graphs and their respective analyses, from which it was possible to draw important conclusions